Developing biochar from potential wastes in Qatar and its revenue potential - Prakash Parthasarathy (10159511) (2023)
Global population growth, booming economies, and modernization are all contributing to increased waste generation, including in Qatar. A more sustainable waste treatment strategy is therefore essential to reaching Qatar's National Vision 2030. Qatar's main waste sources are municipal solid wastes and animal wastes. Both sources have high energy/chemical content and can be converted to fuels and value-added products, particularly biochar. As Qatar continues to expand its arable land, biochar has become one of the most sought-after commodities. As a result, the primary goal of this study is to identify wastes produced in large quantities in Qatar and quantify them. The secondary goal of the research is to estimate the amount of biochar that can be produced from the wastes using pyrolysis technique, as well as the country's biochar revenue potential. A life-cycle assessment of biochar production from all wastes is also performed. Furthermore, the paper discusses market intervention and carbon trading, as well as concerns and limitations associated with biochar application. The findings indicate that Qatar produces 1.8 MT of food waste, the most of any waste produced in the country. Wastepaper has the highest biochar production rate of any waste. It is expected to produce 534,969 T and 224,286 T of biochar at 250 °C and 500 °C, respectively. Among the waste feeds, wastepaper has the greatest potential for generating income from biochar. Its potential revenue is pegged at 107 million USD for 250 °C and 45 million USD for 500 °C annually. Other Information Published in: Energy Conversion and Management: X License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecmx.2023.100467